Development of Prenatal Exercise as a Therapeutic Intervention for Pregnancy-Related Low Back Pain - Ana Yuliana; Nur Hikmah; Darah Ifalahma; Adisti Amalya Putri Handayani; Nurlaila Siti Zamrina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Low back pain is a common complaint among pregnant women in the second and third trimesters due to biomechanical and hormonal changes. Non-pharmacological interventions like prenatal exercise are believed to be effective, though evidence from controlled trials is limited. This study aimed to evaluate the effectiveness of prenatal exercise in reducing low back pain intensity. A quasi-experimental pretest–posttest control group design was used with 30 pregnant women (15 in the intervention group, 15 in the control group), selected by purposive sampling. The inclusion criteria were gestational age of 20–36 weeks, no medical contraindications, and willingness to participate. The intervention group performed prenatal exercises twice a week for 8 weeks (45 minutes per session), while the control group received health education without physical exercise. Pain intensity was measured using the Visual Analogue Scale (VAS). Data analysis was conducted using paired t-test, independent t-test/Mann–Whitney, and ANCOVA to control for age, parity, and BMI. Both groups had homogeneous baseline characteristics (p > 0.05). The intervention group’s pain score decreased from 6.9 ± 1.1 to 3.6 ± 1.0 (Δ = -3.3; p < 0.001), while the control group’s pain score decreased from 6.8 ± 1.2 to 6.3 ± 1.1 (Δ = -0.5; p = 0.09). The difference in pain reduction between groups was significant (p < 0.001). ANCOVA confirmed that prenatal exercise was significantly effective after adjusting for confounders (β = -2.8; p < 0.001). Prenatal exercise is an effective, safe, and affordable intervention for reducing low back pain in pregnant women.